Pengaruh Customer Satisfaction dan Switching Barriers terhadap Customer Loyalty dengan menggunakan Variabel Customer Trust sebagai Variabel Moderating pada Toko Buku Petra Togamas Surabaya - Gisela Ekachristie Risdianto (Jurnal Strategi Pemasaran, 2014)
Today , modern retail business is growing rapidly. Similarly, the growth of retail book stores. As one of the retail book store in Surabaya , Petra Togamas Bookstore should understand what factors that make consumers loyal. forward and growing rapidly. This research aims to analyze the influence of Customer Satisfaction, and Switching Barriers to Customer Loyalty using Customer Trust as moderating variable in Togamas Petra Surabaya Bookstore. This research will be conducted by distributing questionnaires to 100 respondents Bookstore Petra Togamas consumers with convenience sampling. Quantitative analysis with path analysis method were used for technical analysis. The research proves that there is a positif and significant effect of customer satisfaction and switching barriers to customer loyalty. But there is no significant effect of customer trust to customer loyalty.